Idiopathic thrombocytopenic purpura presenting as post-extraction hemorrhage - Martini, Marcelo Zillo [UNESP] (2007)
Aim: The aim of this article is to present a case of idiopathic thrombocytopenic purpura (ITP) in order to emphasize the importance of the clinical exam since the anamnesis leads to a diagnostic hypothesis of ITP. Background: Acute ITP is considered an autoimmune disease characterized by the production of antibodies against platelets, antigens produced by a viral infection, or a platelet sparing drug combination. These antibodies adhere to platelets and are recognized and destroyed by the reticulo-endothelial system. Consequently, the platelet count gradually diminishes and is insufficient for the maintenance of primary hemostasis. Report: A 77-year-old woman presented with post-extraction intermittent bleeding. The physical examination revealed discoloration of the skin, multiple petechiae, hematomas, ecchymosis of the upper lip, bruises all over the body, gingiva that bled spontaneously, and a malformed blood clot at the extraction site of tooth #44. The hematological exams confirmed the hypothesis of ITP. The patient was immediately hospitalized in the Hematology Department of a local hospital and received platelet replacement, hydration, medication, and general care. After the spontaneous bleeding stopped, the malformed clot was removed using alveolar curettage along with a thorough cleaning of the extraction site with a 0.9% saline solution before suturing the wound and prescribing medication. After the sixth day of hospitalization, the patient presented with the following results: Hb: 12.3 mg/dL, Ht: 36.1%, and PC: 87,000 mm3. The patient was then discharged and was placed under outpatient follow-up care. Summary: The importance of the clinical exam must be emphasized since the anamnesis leads to a diagnostic hypothesis of ITP and provides the dental surgeon with an opportunity to make important systemic alterations to improve the prognosis of a patient with ITP.